Peramalan Jumlah Konsumsi Daging Sapi Indonesia Dengan Menggunakan Metode ARIMA - M Fathoni Arnas; Helma Helma; Yenni Kurniawati (Journal of Mathematics UNP, 2019)
Abstract–Each year the consumption of beef in Indonesia is rising, but not followed by the high production of beef in the country. A shortage of beef production which cause the price of beef rises so it can’t beef affordable of society. Therefore be required estimate to amount of beef consumption in Indonesia. This is useful so that the Government can estimate of the consumption of beef is coming so that the Government try to satisfy the supply of beef consumption. One Forecasting method of used is ARIMA method. That formulation of the problem is "How Forecasting the amount of Beef consumption of Indonesia to 12 months ahead, from January 2016 until December 2016 with ARIMA method?” The results obtained from this research was getting Models ARIMA for the real level of 5% and 10% with each form of the equation is and . Keywords–ARIMA Method, Forecasting, BeefConsumption